Tourist Satisfaction Determined by Amenities and Additional Services: Kepuasan Wisatawan Ditentukan oleh Amenitas dan Layanan Tambahan - Rabiatul Adawiyah; Kasmita; Yuliarma; Feri Ferdian (Academia Open, 2025)
General Background: Cultural heritage tourism plays a vital role in supporting local economies and preserving identity, particularly in historically rich areas like Indonesia. Specific Background: The Siak Palace in Riau Province, as a living heritage site from the Malay Kingdom, holds strong potential as a cultural destination but faces challenges in optimizing visitor satisfaction. Knowledge Gap: Previous studies have not simultaneously analyzed the influence of the 4A components (Attraction, Accessibility, Amenities, Ancillary Services) on visitor satisfaction at Malay heritage destinations. Aims: This study investigates the effect of the 4A destination components on tourist satisfaction at the Siak Palace using a quantitative approach. Results: Based on responses from 400 visitors and SmartPLS 4.0 analysis, amenities and ancillary services significantly influenced satisfaction (p < 0.001), while attractions had a smaller positive effect (p = 0.035), and accessibility showed no significant impact (p = 0.408). Novelty: The study applies a robust sample size and advanced SEM-PLS analysis to a culturally specific heritage site, offering empirical insight into underexplored tourism dynamics. Implications: The findings highlight the need to improve facilities and complementary services over transport infrastructure to enhance tourist experiences and sustain heritage-based tourism in Siak.Highlight : This study shows that amenity and ancillary services have the strongest influence on tourist satisfaction at Siak Palace. Accessibility is not significant to satisfaction, indicating that the role of public transportation is not optimal in supporting visits. This study uses a quantitative approach based on SEM-PLS with a large sample (400 respondents), providing strong empirical validity. Keywords : Attraction, Accessibility, Amenities, Ancillary Services, Tourist Satisfaction